Magnitude of anemia and associated factors among pregnant women attending antenatal care in governmental health facilities of Shashemene Town, Oromia region, Ethiopia - Nasir, Mekiya; Ayele, Habtamu Molla; Aman, Rameto; Hussein, Kelil (Frontiers in Public Health, 2024)
Introduction: Anemia in pregnancy is a common issue that affects both the mother's as well as her child's health. Anemia is a global public health issue that affects both developing and developed countries; approximately 1.3 billion people are affected by anemia. Objective: To assess the magnitude and risk factors of anemia among pregnant women attending antenatal care in Shashemene Town, Oromia, Ethiopia.A facility-based cross-sectional study was conducted among 391 pregnant women in Shashemene town in April, 2022. Data were collected using interviewer-administered questionnaires and entered into Epi data 3.1 and exported to SPSS version 22 for analysis. Bivariate logistic regression was performed and variables with a p-value < 0.25 were included in the multivariate logistic regression analysis to identify factors associated with anemia.The adjusted odds ratio (AOR) with 95% CI was calculated and p-value < 0.05 were considered as statistically significant. Finally, the results were presented with narration and descriptive statistics such as tables, graphs and charts.Results: In this study, the prevalence of anemia was 30.9% (95% CI: 26.4%, 35.4%). High dietary diversity (AOR= 0.217, 95% CI 0.105 -0.451), no previous excessive menstrual bleeding (AOR= 0.162, 95% CI 0.076 -0.345), and age 25-34 years (AOR= 0.391, 95% CI 0.173 -0.883) and age >= 35 years (AOR= 0.068, 95% CI 0.011 -0.444) were significantly associated with reducing the risk of Anemia While MUAC < 23cm (AOR= 4.939, 95% CI 2.330 -10.469), no use of contraceptives (AOR= 4.935, 95% CI 2.207-11.032), and no iron supplementation use (AOR= 3.588, 95% CI 1.794 -7.175) were significantly associated with increasing the risk of Anemia.The magnitude of Anemia was found to be a moderate public health problem in the study area as per the WHO classification. High dietary diversity, no previous excessive menstrual bleeding, and age were significantly associated with reducing the risk of anemia While MUAC < 23cm, no contraceptive use, and no use of iron supplementation were significantly associated with increasing the risk of anemia. As a result, encouraging pregnant women to eat diverse diets, counseling on the benefits of using family planning, iron-folic acid supplements, and improving women's education and empowerment are essential.